Low-temperature-resistant high-impact high-performance polypropylene safety helmet shell material and preparation method thereof
Patent Information
- Application Number
- CN202611357579.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-20
AI Technical Summary
通过引入低玻璃化转变温度的柔性聚合物,可以改善聚丙烯在低温下的形变能力,但柔性聚合物加入量过大时,又容易降低材料的弯曲刚度、尺寸稳定性和抗穿刺能力
1、耐低温聚烯烃改性颗粒进入聚丙烯基体后,POE形成能够在低温下保持形变能力的柔韧微区,LLDPE中的结晶链段则对该柔韧微区起到物理连接和形态稳定作用。在低温冲击载荷作用下,这些柔韧微区可以先于聚丙烯基体发生拉伸和适度空穴化,缓解裂纹尖端的三轴应力,并诱导周围聚丙烯产生较大范围的剪切屈服,使原本集中在缺口附近的冲击能量分散到更大的材料体积中。POE与LLDPE配合使用,既保留了柔韧相的低温耗能能力,又降低了单独大量加入低模量弹性体所造成的刚度下降,从而改善聚丙烯在低温环境下容易脆裂的问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-performance polypropylene materials technology, specifically to a low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material and its preparation method. Background Technology
[0002] Polypropylene (PP) has advantages such as low density, chemical resistance, ease of injection molding, and low raw material cost, making it suitable for lightweight manufacturing of helmet shells. During use, helmet shells not only need to withstand the instantaneous impact of falling objects but also must maintain sufficient rigidity and puncture resistance to prevent the impact load from being directly transmitted to the wearer's head. Therefore, the shell material needs to possess impact absorption capacity, structural strength, and molding stability simultaneously.
[0003] Polypropylene is a semi-crystalline polymer. As the ambient temperature decreases, the mobility of its amorphous molecular chain segments weakens, consequently reducing the material's ability to undergo plastic deformation and disperse impact stress. When impacted at notches, fiber ends, or areas of localized thickness variation, cracks tend to propagate rapidly, leading to low-temperature brittle fracture of the shell. Introducing flexible polymers with low glass transition temperatures can improve polypropylene's deformation capacity at low temperatures; however, excessive addition of flexible polymers can easily reduce the material's flexural stiffness, dimensional stability, and puncture resistance.
[0004] Using high-strength fibers to construct load-bearing structures can improve the stiffness of the shell and its ability to resist concentrated impacts. However, there are significant performance differences between rigid fibers and the polypropylene matrix. When the fiber interface is too weak, impact loads are difficult to transfer effectively; when the fiber interface is too strong or lacks a flexible buffer layer, the fiber ends and surrounding areas can easily restrict the deformation of the low-temperature flexible phase, preventing the flexible phase from fully absorbing impact energy. Therefore, directly mixing low-temperature flexible materials with rigid reinforcing fibers does not naturally achieve a balance between low-temperature toughness, impact strength, and structural stiffness.
[0005] Based on the above, the core technical problem to be solved in this application is how to construct a flexible phase that can deform and dissipate energy at low temperatures and a fiber-reinforced structure that can bear and disperse impact loads in the polypropylene helmet shell material. At the same time, through reasonable fiber surface coating and hierarchical interface design, the local constraint of rigid fibers on the flexible phase at low temperatures can be reduced, so that the two types of structures can work together. In this way, the low-temperature resistance and impact resistance of the polypropylene helmet shell material can be improved without significantly sacrificing the shell stiffness, molding performance and cost controllability. Summary of the Invention
[0006] The purpose of this invention is to provide a low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material and its preparation method, so as to solve the technical problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a low-temperature resistant, high-impact resistant, and high-performance polypropylene safety helmet shell material includes the following steps: (1) Ethylene-octene copolymer polyolefin elastomer, linear low-density polyethylene, maleic anhydride, styrene and dicumyl peroxide are reacted and extruded, and then devolatilized and granulated to obtain low-temperature resistant polyolefin modified particles. (2) The unsized basalt short-cut fibers were treated with the hydrolysate of γ-glycidyl oxypropyltrimethoxysilane, and then the basalt short-cut fibers were coated with carboxylated styrene-butadiene latex containing 2-methylimidazole. After dehydration and heat treatment, elastic coated basalt fibers were obtained. (3) The elastic coated basalt fiber is first melt-coated with ethylene-vinyl acetate copolymer, and then melt-coated with low-density polyethylene after cooling to obtain sequentially coated fiber masterbatch; (4) The polypropylene and the low-temperature resistant polyolefin modified particles are melt-mixed, and the sequentially coated fiber masterbatch is added in the later stage of the melt mixing. The mixture is then extruded and granulated to obtain the polypropylene safety helmet shell material.
[0008] Preferably, in step (1), based on a total of 100 parts by mass of the ethylene-octene copolymer polyolefin elastomer and linear low-density polyethylene, the ethylene-octene copolymer polyolefin elastomer comprises 75-85 parts by mass, the linear low-density polyethylene comprises 15-25 parts by mass, the maleic anhydride comprises 1.0-1.3 parts by mass, the styrene comprises 1.05-1.40 parts by mass, and the dicumyl peroxide comprises 0.06-0.10 parts by mass as an effective component; the molar ratio of maleic anhydride to styrene is 0.9:1 to 1.1:1.
[0009] Preferably, step (1) includes: Maleic anhydride is added to styrene and stirred at 55-60°C under nitrogen protection to form a clear solution; the ethylene-octene copolymer polyolefin elastomer and linear low-density polyethylene are added to a twin-screw extruder and, after they melt, the clear solution is injected into the reaction section filled with polymer melt, and dicumyl peroxide is added by an independent feeding device. The melt temperature in the reaction section is 177-183℃, and the residence time of the material in the reaction section is 90-120 seconds. After the reaction is completed, the material is devolatilized under a gauge pressure of -0.08 to -0.06 MPa, and then 0.08-0.12 parts by weight of antioxidant 1010 and antioxidant 168 are added. The mixture is then extruded and granulated.
[0010] Preferably, in step (2), the basalt short-cut fiber is 100 parts by weight, the γ-glycidyl etheroxypropyltrimethoxysilane is 0.8 to 1.0 parts by weight, the carboxylated styrene-butadiene latex is 8 parts by weight based on dry rubber, and the 2-methylimidazole is 0.016 to 0.020 parts by weight. The basalt short-cut fibers have a length of 2-4 mm and a single filament diameter of 9-17 μm; the carboxylated styrene-butadiene latex has a dry amino acid value of 20-30 mg KOH / g, a gel content of not less than 80%, and a glass transition temperature of not more than -30℃.
[0011] Preferably, step (2) includes: The γ-glycidyl etheroxypropyltrimethoxysilane was prepared into an ethanol / water solution with a mass concentration of 8% to 12%, wherein the mass ratio of ethanol to water was 95:5. The pH value was adjusted to 4.5 to 5.0 with acetic acid. After pre-hydrolyzing at 25°C for 20 to 30 minutes, it was sprayed onto the surface of basalt chopped fibers, dried at 80°C for 1 hour, and then treated at 105 to 110°C for 30 minutes. 2-Methylimidazole was dissolved in water and then added to carboxylated styrene-butadiene latex. The resulting carboxylated styrene-butadiene latex was sprayed onto the surface of basalt short-cut fibers treated with the hydrolysate. The fibers were first dehydrated at 60–80°C, then heat-treated at 135–145°C for 45–60 minutes under nitrogen protection, and finally vacuum dried until the moisture content was no higher than 0.2%.
[0012] Preferably, in step (3), the polypropylene used in step (4) is 100 parts by weight, the elastic coated basalt fiber is 8 to 12 parts by weight, the ethylene-vinyl acetate copolymer is 1.2 to 2.0 parts by weight, and the low-density polyethylene is 1.6 to 2.8 parts by weight. The vinyl acetate content of the ethylene-vinyl acetate copolymer is 14% to 18%, and the melt mass flow rate at 190°C and 2.16 kg load is 6 to 12 g / 10 min. The low-density polyethylene is a long-branched ethylene homopolymer obtained by high-pressure free radical polymerization, with a density of 0.918–0.924 g / cm³. 3 The melt mass flow rate at 190℃ and 2.16kg load is 4~10g / 10min.
[0013] Preferably, step (3) includes: Ethylene-vinyl acetate copolymer with a particle size of no more than 300 μm was added to the elastically coated basalt fiber and mixed at 108–118 °C and 60–100 r / min for 6–8 minutes. After the first melt coating was completed, the mixture was cooled to below 40 °C. Then add low-density polyethylene with a particle size of no more than 300 μm, mix at 125-135℃ and 60-100 r / min for 5-8 minutes, cool after the second melt coating is completed, and obtain the sequentially coated fiber masterbatch.
[0014] Preferably, in step (4), polypropylene is 100 parts by weight, and the low-temperature resistant polyolefin modified particles are 12-16 parts by weight; the sequentially coated fiber masterbatch includes 8-12 parts by weight of elastic coated basalt fiber, 1.2-2.0 parts by weight of ethylene-vinyl acetate copolymer and 1.6-2.8 parts by weight of low-density polyethylene; antioxidant 1010 and antioxidant 168 are also added in 0.15-0.20 parts by weight each. The polypropylene, low-temperature resistant polyolefin modified particles, antioxidant 1010 and antioxidant 168 are added from the main feed port of the twin-screw extruder, and the sequentially coated fiber masterbatch is added from the rear side feed port after the vacuum devouring port. The temperatures of each zone of the twin-screw extruder are 150–160℃, 165–175℃, 175–185℃, 185–195℃, 185–195℃, and 180–190℃ respectively, and the melt temperature is not higher than 195℃. The residence time after the sequentially coated fiber masterbatch is added is 30–60 seconds.
[0015] Preferably, the polypropylene helmet shell material obtained in step (4) is dried at 75-85°C for 2 hours and then injection molded to obtain a polypropylene helmet shell. The injection molding machine has a barrel temperature of 175–195℃, a melt temperature not exceeding 195℃, a mold temperature of 35–45℃, an injection pressure of 70–90MPa, a holding time of 8–12 seconds, and a cooling time of 20–35 seconds.
[0016] A low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material is prepared by the method described above.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. After low-temperature resistant polyolefin (POE) modified particles are incorporated into the polypropylene matrix, POE forms flexible microdomains that maintain their deformability at low temperatures. The crystalline segments in LLDPE then provide physical connection and morphological stability to these flexible microdomains. Under low-temperature impact loads, these flexible microdomains can undergo stretching and moderate cavitation before the polypropylene matrix, relieving triaxial stress at the crack tip and inducing a larger range of shear yielding in the surrounding polypropylene. This disperses the impact energy originally concentrated near the notch into a larger material volume. The combined use of POE and LLDPE retains the low-temperature energy dissipation capability of the flexible phase while reducing the stiffness decrease caused by adding large amounts of low-modulus elastomers alone, thus improving the problem of polypropylene's brittleness at low temperatures.
[0018] 2. The elastically coated basalt fiber simultaneously undertakes load transfer and impact energy dissipation functions within the material. Basalt fiber possesses high strength and modulus, enabling it to distribute concentrated impact loads on the shell and force cracks to change their propagation direction, extending the crack propagation path. The carboxylated styrene-butadiene rubber coating on the fiber surface forms a flexible buffer zone between the rigid fiber and the polypropylene matrix. When cracks propagate to the vicinity of the fiber, the coating layer can reduce local stress concentration at the fiber ends through its own deformation, and allow interface debonding, fiber pull-out, and interfacial friction to occur under controlled conditions, thereby dissipating more impact energy. This structure avoids the brittle interface resulting from direct contact between rigid basalt fiber and the polypropylene matrix, while retaining the fiber's reinforcing effect on shell stiffness, puncture resistance, and load dispersion.
[0019] 3. When elastic-coated basalt fibers are directly composited with the POE / LLDPE flexible phase, the high-modulus basalt fibers still exert local constraints on the adjacent flexible phase, preventing the flexible phase from fully stretching and deforming to dissipate energy during low-temperature impact, thus partially offsetting the already achieved low-temperature ductility. To address this issue, an EVA-enriched layer is first formed on the surface of the elastic-coated basalt fibers, followed by an LDPE-enriched layer. EVA contains a certain proportion of vinyl acetate structure, which has higher polarity than polypropylene and polyethylene, thus enabling it to better wet carboxylated styrene-butadiene rubber and silane-treated surfaces, forming a continuous and soft inner buffer region on the outside of the rigid fibers. However, if EVA is used alone, the interfacial connection between its outer side and the non-polar polypropylene and POE / LLDPE flexible phase remains limited, easily leading to new interfaces that abruptly alter performance. LDPE has a long-chain branched polyethylene structure. Its ethylene segments have good segmental affinity and limited interdiffusion ability with the ethylene segments in EVA and the flexible phases of POE and LLDPE, making it suitable as an outer transition material. However, LDPE itself has low polarity. If it is directly coated with carboxylated styrene-butadiene rubber and silane-treated surfaces, the wetting and adhesion abilities are insufficient, making it difficult to form a stable buffer interface. After coating with EVA inside and LDPE outside, EVA is responsible for connecting the more polar fiber-coated surface, while LDPE is responsible for connecting the external non-polar polyolefin matrix. Together, they form an interface structure that gradually decreases in polarity and transitions in modulus from the fiber surface to the polypropylene matrix. This synergistic structure not only reduces the local confinement of the rigid fiber on the surrounding flexible phase, allowing the POE / LLDPE microregions to fully participate in deformation energy dissipation during low-temperature impact, but also avoids the inability to transfer loads due to excessively soft interfaces. This allows the impact load to be transferred sequentially through the polypropylene matrix, the outer transition region of LDPE, and the inner buffer region of EVA to the basalt fiber, thus achieving a good balance between low-temperature toughness, impact strength, and shell stiffness. Attached Figure Description
[0020] Figure 1This is a low-magnification SEM image of the low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material prepared in Example 1 of the present invention.
[0021] Figure 2 This is a high-magnification SEM image of the low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material prepared in Example 1 of the present invention. Detailed Implementation
[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0023] Example 1 A method for preparing a low-temperature resistant, high-impact resistant, and high-performance polypropylene safety helmet shell material includes the following steps: 1. Preparation of Low-Temperature Resistant Polyolefin Modified Particles Weigh out 75.000 kg of POE granules, 24.910 kg of LLDPE granules, and 0.150 kg of 40 wt% DCP-LLDPE masterbatch. The DCP-LLDPE masterbatch contains 0.060 kg of DCP and 0.090 kg of LLDPE carrier, therefore the total mass of POE and LLDPE is 100.000 kg.
[0024] Weigh 1.000 kg of maleic anhydride and 1.050 kg of styrene, and stir at 55°C under nitrogen protection until a clear solution is formed; the molar ratio of maleic anhydride to styrene is 1.012:1.
[0025] POE and 24.910 kg LLDPE were added through the main feed port of a twin-screw extruder. The extruder temperatures from the feed section to the die head were set sequentially to 110℃, 145℃, 165℃, 177℃, 177℃, 177℃, 170℃, 165℃, and 170℃, with a screw speed of 350 r / min. After the polymer melted, maleic anhydride / styrene solution and 0.150 kg DCP-LLDPE masterbatch were added to the reaction section through independent feeders, with the residence time in the reaction section controlled at 120 seconds. After the reaction, devolatilization was performed under a gauge pressure of -0.08 MPa. Then, 0.080 kg each of antioxidant 1010 and antioxidant 168 were added downstream. The mixture was extruded, water-cooled, and pelletized to obtain low-temperature resistant polyolefin modified granules.
[0026] 2. Preparation of elastically coated basalt fibers Weigh 100.000 kg of unsized basalt short-cut fibers with a length of 2 mm and a single filament diameter of 9 μm.
[0027] 0.800 kg of KH-560, 8.740 kg of anhydrous ethanol, and 0.460 kg of deionized water were mixed to obtain 10.000 kg of a treatment solution with a KH-560 concentration of 8 wt%, wherein the mass ratio of ethanol to water was 95:5. The pH was adjusted to 4.5 by dropwise addition of glacial acetic acid with a purity of not less than 99.5%. After pre-hydrolysis at 25°C for 20 minutes, the entire treatment solution was immediately sprayed onto the surface of basalt fibers that were being slowly agitated. The sprayed fibers were dried at 80°C for 1 hour, and then treated at 105°C for 30 minutes.
[0028] 16.000 kg of carboxylated styrene-butadiene latex with a solid content of 50 wt%, a dry basalt acid value of 20 mg KOH / g, a gel content of 80%, and a glass transition temperature of -30℃ was selected, corresponding to a dry rubber mass of 8.000 kg. 0.016 kg of 2-methylimidazole was dissolved in 0.384 kg of deionized water to prepare a 0.400 kg aqueous solution with a mass concentration of 4 wt%, which was then completely added to the latex. The resulting latex was sprayed onto the fiber surface treated with KH-560, dehydrated at 60℃ for 2.5 hours, then heat-treated at 135℃ for 45 minutes under nitrogen protection, and finally vacuum-dried at 60℃ and a gauge pressure of -0.08 MPa for 2 hours. The release condition was a moisture content not exceeding 0.2%, resulting in elastically coated basalt fibers.
[0029] 3. Preparation of sequentially coated fiber masterbatch Based on the final amount of 100,000 kg of polypropylene, weigh out 8,000 kg of the above-mentioned elastic coated basalt fiber, 1,200 kg of EVA powder and 1,600 kg of LDPE powder.
[0030] The EVA contains 14 wt% vinyl acetate and has a melt flow rate of 6 g / 10 min at 190°C and a load of 2.16 kg; LDPE is a long-branched ethylene homopolymer polymerized under high pressure and free radical polymerization, with a density of 0.918 g / cm³. 3 The melt mass flow rate at 190℃ and 2.16kg load is 4g / 10min. The maximum particle size of both powders is 300μm.
[0031] Elastic coated basalt fiber and EVA were added to a low-shear hot mixer and mixed for 6 minutes at 108°C and 60 r / min, then cooled to 38°C; LDPE was then added and mixed for 5 minutes at 125°C and 60 r / min, then cooled to obtain 10.800 kg of sequentially coated fiber masterbatch.
[0032] 4. Composite granulation Weigh 100.000 kg of injection-grade polypropylene with a melt flow rate of 8 g / 10 min, a test condition of 230 °C and a load of 2.16 kg, 12.000 kg of the low-temperature resistant polyolefin modified granules obtained in step 1, and 0.150 kg each of antioxidant 1010 and antioxidant 168.
[0033] Polypropylene, low-temperature resistant polyolefin modified granules, and two antioxidants were added through the main feed port of a twin-screw extruder. 10.800 kg of sequentially coated fiber masterbatch obtained in step 3 was added through a side feed port after the vacuum devolatilization port. The six temperature zones of the extruder were set sequentially to 150℃, 165℃, 175℃, 185℃, 185℃, and 180℃, with the melt temperature controlled below 195℃. The residence time after adding the sequentially coated fiber masterbatch was 30 seconds. The extrudate was water-cooled and pelletized to obtain shell material granules.
[0034] 5. Injection molding The shell material granules were dried at 75℃ for 2 hours. The temperatures of each section of the injection molding machine barrel were set to 175℃, 180℃, 185℃ and 190℃ respectively, the melt temperature was controlled below 195℃, the mold temperature was 35℃, the injection pressure was 70MPa, the holding time was 8 seconds and the cooling time was 20 seconds. The polypropylene safety helmet shell was obtained by injection molding.
[0035] Example 2 A method for preparing a low-temperature resistant, high-impact resistant, and high-performance polypropylene safety helmet shell material includes the following steps: 1. Preparation of Low-Temperature Resistant Polyolefin Modified Particles Weigh out 80.000 kg of POE granules, 19.880 kg of LLDPE granules, and 0.200 kg of 40 wt% DCP-LLDPE masterbatch. The masterbatch contains 0.080 kg of DCP and 0.120 kg of LLDPE carrier, for a total of 100.000 kg of POE and LLDPE.
[0036] Weigh 1.187 kg of maleic anhydride and 1.400 kg of styrene, and stir at 58 °C under nitrogen protection until clear; the molar ratio of maleic anhydride to styrene is 0.901:1.
[0037] POE and 19.880 kg of LLDPE were added through the main feed port of a twin-screw extruder. The extruder temperatures from the feed section to the die head were set sequentially to 110℃, 150℃, 170℃, 180℃, 180℃, 180℃, 175℃, 170℃, and 175℃, with a screw speed of 400 r / min. After the polymer melted, maleic anhydride / styrene solution and 0.200 kg of DCP-LLDPE masterbatch were added to the reaction section, with a residence time of 105 seconds. After the reaction, devolatilization was performed under a gauge pressure of -0.07 MPa. Then, 0.100 kg each of antioxidant 1010 and antioxidant 168 were added downstream. The mixture was extruded, water-cooled, and pelletized to obtain low-temperature resistant modified polyolefin granules.
[0038] 2. Preparation of elastically coated basalt fibers Weigh 100.000 kg of unsized basalt short fibers with a length of 3 mm and a single filament diameter of 13 μm.
[0039] 0.900 kg of KH-560, 7.695 kg of anhydrous ethanol, and 0.405 kg of deionized water were mixed to obtain 9.000 kg of a treatment solution with a KH-560 concentration of 10 wt%. The pH was adjusted to 4.7 by dropwise addition of glacial acetic acid with a purity of not less than 99.5%. After pre-hydrolyzing at 25°C for 25 minutes, the entire treatment solution was sprayed onto the surface of basalt fibers. Subsequently, the fibers were dried at 80°C for 1 hour, followed by treatment at 108°C for 30 minutes.
[0040] 16.000 kg of carboxylated styrene-butadiene latex with a solid content of 50 wt%, a dry basalt acid value of 25 mg KOH / g, a gel content of 85%, and a glass transition temperature of -35℃ was selected. 0.018 kg of 2-methylimidazole was dissolved in 0.432 kg of deionized water to prepare a 0.450 kg aqueous solution with a mass concentration of 4 wt%, which was then completely added to the latex. The latex was sprayed onto the fiber surface, dehydrated at 70℃ for 2 hours, then heat-treated at 140℃ for 52 minutes under nitrogen protection, and finally vacuum-dried at 60℃ and a gauge pressure of -0.08 MPa for 2 hours. The release condition was a moisture content not exceeding 0.2%, resulting in elastically coated basalt fibers.
[0041] 3. Preparation of sequentially coated fiber masterbatch Based on the final amount of 100,000 kg of polypropylene, weigh out 10,000 kg of elastically coated basalt fiber, 1,600 kg of EVA powder and 2,200 kg of LDPE powder.
[0042] The EVA contains 16 wt% vinyl acetate and has a melt flow rate of 9 g / 10 min at 190 °C and a load of 2.16 kg; LDPE is a long-branched ethylene homopolymer polymerized under high pressure and free radical polymerization, with a density of 0.921 g / cm³. 3The melt mass flow rate at 190℃ and 2.16kg load was 7g / 10min. The maximum particle size of both powders was 250μm.
[0043] Elastic coated basalt fiber and EVA were hot-mixed at 113℃ and 80r / min for 7 minutes and then cooled to 35℃. LDPE was then added and hot-mixed at 130℃ and 80r / min for 6.5 minutes and then cooled to obtain 13.800kg of sequentially coated fiber masterbatch.
[0044] 4. Composite granulation Weigh out 100.000 kg of injection-molding grade polypropylene, 14.000 kg of low-temperature resistant polyolefin modified granules, and 0.180 kg each of antioxidant 1010 and antioxidant 168. The melt flow rate of the polypropylene is 8 g / 10 min, and the test conditions are 230℃ and 2.16 kg load.
[0045] Polypropylene, low-temperature resistant polyolefin modified granules, and two antioxidants were added through the main feed port of a twin-screw extruder. 13,800 kg of sequentially coated fiber masterbatch was added through a side feed port after the vacuum devolatilization port. The extruder's six temperature zones were set sequentially to 155℃, 170℃, 180℃, 190℃, 190℃, and 185℃, with the melt temperature controlled below 195℃. The residence time after masterbatch addition was 45 seconds. The extrudate was water-cooled and pelletized to obtain shell material granules.
[0046] 5. Injection molding The shell material granules were dried at 80℃ for 2 hours. The temperatures of each section of the injection molding machine barrel were set to 180℃, 185℃, 190℃ and 192℃ respectively. The melt temperature was controlled below 195℃, the mold temperature was 40℃, the injection pressure was 80MPa, the holding time was 10 seconds and the cooling time was 27 seconds. The polypropylene safety helmet shell was obtained by injection molding.
[0047] Example 3 A method for preparing a low-temperature resistant, high-impact resistant, and high-performance polypropylene safety helmet shell material includes the following steps: 1. Preparation of Low-Temperature Resistant Polyolefin Modified Particles Weigh out 85.000 kg of POE granules, 14.850 kg of LLDPE granules, and 0.250 kg of 40 wt% DCP-LLDPE masterbatch. The masterbatch contains 0.100 kg of DCP and 0.150 kg of LLDPE carrier, for a total of 100.000 kg of POE and LLDPE.
[0048] Weigh 1.300 kg of maleic anhydride and 1.256 kg of styrene, and stir at 60°C under nitrogen protection until clear; the molar ratio of maleic anhydride to styrene is 1.099:1.
[0049] POE and 14.850 kg LLDPE were added through the main feed port of a twin-screw extruder. The extruder temperatures from the feed section to the die head were set sequentially to 120℃, 155℃, 175℃, 183℃, 183℃, 183℃, 178℃, 175℃, and 180℃, with a screw speed of 450 r / min. After the polymer melted, maleic anhydride / styrene solution and 0.250 kg DCP-LLDPE masterbatch were added to the reaction section, with a residence time of 90 seconds. After the reaction, devolatilization was performed under a gauge pressure of -0.06 MPa. Then, 0.120 kg each of antioxidant 1010 and antioxidant 168 were added downstream. The mixture was extruded, water-cooled, and pelletized to obtain low-temperature resistant modified polyolefin granules.
[0050] 2. Preparation of elastically coated basalt fibers Weigh 100.000 kg of unsized basalt short fibers with a length of 4 mm and a single filament diameter of 17 μm.
[0051] 1.000 kg of KH-560, 6.967 kg of anhydrous ethanol, and 0.367 kg of deionized water were mixed to obtain 8.334 kg of a treatment solution with a KH-560 concentration of 12.0 wt%. The pH was adjusted to 5.0 by dropwise addition of glacial acetic acid with a purity of not less than 99.5%. After pre-hydrolysis at 25°C for 30 minutes, the entire treatment solution was sprayed onto the surface of basalt fibers. Subsequently, the fibers were dried at 80°C for 1 hour, followed by treatment at 110°C for 30 minutes.
[0052] 16.000 kg of carboxylated styrene-butadiene latex with a solid content of 50 wt%, a dry amino acid value of 30 mg KOH / g, a gel content of 90%, and a glass transition temperature of -40℃ was selected. 0.020 kg of 2-methylimidazole was dissolved in 0.480 kg of deionized water to prepare a 0.500 kg aqueous solution with a mass concentration of 4 wt%, which was then completely added to the latex. The latex was sprayed onto the fiber surface, dehydrated at 80℃ for 1.5 hours, then heat-treated at 145℃ for 60 minutes under nitrogen protection, and finally vacuum-dried at 60℃ and a gauge pressure of -0.08 MPa for 2 hours. The release condition was a moisture content not exceeding 0.2%, resulting in elastically coated basalt fibers.
[0053] 3. Preparation of sequentially coated fiber masterbatch Based on the final amount of 100,000 kg of polypropylene, weigh out 12,000 kg of elastically coated basalt fiber, 2,000 kg of EVA powder and 2,800 kg of LDPE powder.
[0054] The EVA contains 18 wt% vinyl acetate and has a melt flow rate of 12 g / 10 min at 190 °C and a load of 2.16 kg; LDPE is a long-branched ethylene homopolymer polymerized under high pressure and free radical polymerization, with a density of 0.924 g / cm³.3 The melt mass flow rate at 190℃ and 2.16kg load was 10g / 10min. The maximum particle size of both powders was 200μm.
[0055] Elastic coated basalt fiber and EVA were hot-mixed at 118℃ and 100r / min for 8 minutes and then cooled to 30℃. LDPE was then added and hot-mixed at 135℃ and 100r / min for 8 minutes and then cooled to obtain 16.800kg of sequentially coated fiber masterbatch.
[0056] 4. Composite granulation Weigh out 100.000 kg of injection molding grade polypropylene, 16.000 kg of low-temperature resistant polyolefin modified granules, and 0.200 kg each of antioxidant 1010 and antioxidant 168. The melt flow rate of polypropylene is 8 g / 10 min, and the test conditions are 230℃ and 2.16 kg load.
[0057] Polypropylene, low-temperature resistant polyolefin modified granules, and two antioxidants were added through the main feed port of a twin-screw extruder. 16,800 kg of sequentially coated fiber masterbatch was added through a side feed port after the vacuum devolatilization port. The extruder's six temperature zones were set sequentially to 160℃, 175℃, 185℃, 195℃, 195℃, and 190℃. The melt temperature was controlled below 195℃ by adjusting the feed rate and screw speed. The residence time after masterbatch addition was 60 seconds. The extrudate was water-cooled and pelletized to obtain shell material granules.
[0058] 5. Injection molding The shell material granules were dried at 85℃ for 2 hours. The temperatures of each section of the injection molding machine barrel were set to 185℃, 190℃, 195℃ and 195℃ respectively. The melt temperature was controlled below 195℃, the mold temperature was 45℃, the injection pressure was 90MPa, the holding time was 12 seconds and the cooling time was 35 seconds. The polypropylene safety helmet shell was obtained by injection molding.
[0059] Comparative Example 1: 12,000 kg of polypropylene was used to replace the 12,000 kg of low-temperature resistant polyolefin modified particles in Example 1. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0060] Comparative Example 2: 12,000 kg of polyolefin mixed particles with a POE to LLDPE mass ratio of 75:25 and without maleic anhydride and styrene reaction grafting were used to replace the low-temperature resistant polyolefin modified particles in Example 1. The amounts of other raw materials and preparation steps were the same as in Example 1.
[0061] Comparative Example 3: 8,000 kg of untreated basalt short-cut fibers of the same length and monofilament diameter were used to replace the elastic-coated basalt fibers in Example 1. The fiber masterbatch was then prepared according to the EVA and LDPE coating process in Example 1. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0062] Comparative Example 4: 8,000 kg of basalt short-cut fibers treated only with KH-560 but not coated with carboxylated styrene-butadiene latex were used to replace the elastic coated basalt fibers in Example 1. The amounts of other raw materials and preparation steps were the same as in Example 1.
[0063] Comparative Example 5: The sequential coating process of EVA and LDPE in Example 1 was cancelled. 2.800 kg of polypropylene was used to replace EVA and LDPE. 8.000 kg of elastic coated basalt fiber was directly fed from the back side of the twin-screw extruder. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0064] Comparative Example 6: The EVA and LDPE in Example 1 were replaced with a total of 2.800 kg of EVA, and this EVA was used to perform single-layer melt coating on 8.000 kg of elastic coated basalt fiber. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0065] Comparative Example 7: The EVA and LDPE in Example 1 were replaced with a total of 2.800 kg of LDPE, and this LDPE was used to perform single-layer melt coating on 8.000 kg of elastic coated basalt fiber. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0066] Comparative Example 8: The EVA content was kept at 1.200 kg and the LDPE content at 1.600 kg, but the elastic basalt fiber was first melt-coated with LDPE, and then melt-coated with EVA after cooling. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0067] Comparative Example 9: EVA was kept at 1.200 kg and LDPE at 1.600 kg, but no pre-coating was performed. Instead, EVA, LDPE and 8.000 kg of elastic coated basalt fiber were added from the rear section of the twin-screw extruder. The amount of other raw materials and the preparation steps were the same as in Example 1.
[0068] Performance testing Material particles obtained from Examples 1-3 and Comparative Examples 1-9 were dried at 80±2℃ for 2 hours. Standard samples were prepared using the same injection molding machine under uniform conditions: barrel temperatures of 180℃, 185℃, 190℃, and 190℃; mold temperature of 40±2℃; injection pressure of 80MPa; holding pressure of 10s; and cooling of 28s. Sample preparation was performed according to GB / T 2546.2-2022 and GB / T 17037.1-2019. The injection flow direction of each sample was kept consistent, and the notches of the impact samples were machined after injection molding. Except for the low-temperature impact sample, all samples were conditioned in an environment of 23±2℃ and 50±10% relative humidity for no less than 16 hours according to GB / T 2918-2018 before testing.
[0069] Tensile properties: Tested according to GB / T 1040.1-2025 and GB / T 1040.2-2022, using type 1A injection molded specimens. The initial spacing and gauge length of the clamps are set according to the standard specifications. The test speed is 50 mm / min, and 5 valid specimens are tested per group. The tensile yield stress is taken as the stress at which the specimen yields. If the specimen breaks directly without obvious yielding, the maximum tensile stress should be reported and the failure mode should be noted. The two results should not be combined for calculation.
[0070] Bending modulus: Tested according to GB / T 9341-2008, using 80mm×10mm×4mm long strip specimens with a span of 64mm, three-point bending test speed of 2mm / min, 5 valid specimens per group, the bending modulus is calculated based on the slope of the stress-strain curve in the bending strain range of 0.05%~0.25%, and the result is expressed in MPa.
[0071] Notched impact strength of simply supported beams at 23℃: Tested according to GB / T 1043.1-2008, using 80 mm × 10 mm × 4 mm type 1eA specimens. A type A V-shaped notch was machined into the width of the specimen, with a notch angle of 45°±1°, a notch bottom radius of 0.25±0.05 mm, a notch depth of 2.0 mm, and a remaining width at the notch of 8.0±0.2 mm. Lateral impact was performed using a 2J pendulum. Ten valid specimens were tested in each group. The notched impact strength of the simply supported beam was calculated, and the failure type (complete fracture, partial fracture, or no fracture) was recorded.
[0072] -30℃ Notched Impact Strength of Simply Supported Beams: The specimen size, notch type, impact direction, and calculation method are the same as those for the 23℃ Notched Impact Test of Simply Supported Beams. After notch preparation and standard environmental conditioning, the specimens are placed in a -30±2℃ circulating air cryogenic chamber for 4 hours. Insulated clamps are used for sampling, and the impact is completed within 10 seconds. Specimens that are not tested within 10 seconds are returned to the cryogenic chamber for at least 15 minutes of conditioning. A 0.5J pendulum is used, and 10 valid specimens are tested per group. Condensation on the specimen surface is avoided during transfer.
[0073] Load deformation temperature: Tested according to GB / T 1634.1-2025 and GB / T 1634.2-2019, using 80mm×10mm×4mm specimens, loaded in a flat manner with a span of 64mm, bending stress of 0.45MPa, and heating rate of 120±10℃ / h. The temperature at which the specimen produces a specified deflection of 0.34mm is taken as the load deformation temperature, denoted as Tf0.45. Each test group shall have no less than 3 valid specimens.
[0074] Melt flow rate (MFR): Tested according to Method A of GB / T 3682.1-2018, with a test temperature of 230±0.5℃ and a nominal load of 2.16 kg. The sample was preheated for 5 minutes after being loaded into the barrel before cutting. Each sample was loaded three times independently, retaining at least five segments of effective extrudate each time. The MFR was calculated based on the weighing results, in g / 10min. The final polypropylene composite material must not be tested under the 190℃ conditions used for EVA or LDPE raw materials.
[0075] Table 1 Compared to Comparative Example 1, which did not contain the low-temperature resistant polyolefin modified particles, the notched impact strength of the simply supported beam at 23°C in Example 1 increased from 9.3 kJ / m. 2 Increased to 21.9 kJ / m 2 The notched impact strength of a simply supported beam at -30℃ is 2.4 kJ / m 2 Increased to 8.7 kJ / m 2 Meanwhile, the tensile yield stress, flexural modulus, and Tf0.45 decreased. This change aligns with the fundamental principle that flexible polyolefin phases increase impact energy dissipation while reducing matrix rigidity. Comparative Example 2, while retaining the same mass ratio of POE and LLDPE, employed a physical blending route, achieving an impact strength of 7.0 kJ / m² at -30°C. 2 The values were lower than in Example 1, and the tensile yield stress and flexural modulus were also relatively low, indicating that the reactive extrusion modification route reflects a comprehensive improvement in interfacial state, dispersion morphology and rheological properties in the data.
[0076] Comparative Example 3 used untreated basalt fibers, while Comparative Example 4 used basalt fibers that had only been treated with KH-560 without forming a carboxylated styrene-butadiene latex elastic coating. Both examples showed higher flexural modulus and load deformation temperature than Example 1, but their notched impact strength at -30℃ was only 4.4 kJ / m. 2 and 5.0 kJ / m 2 This trend indicates that rigid fibers or stiff fiber interfaces are beneficial for load transfer, but can easily lead to high local stress near the fiber ends; carboxylated styrene-butadiene latex coatings can provide a deformable buffer zone between the fiber and the polyolefin matrix, thereby improving the balance between rigidity retention and impact energy dissipation.
[0077] Example 1 was compared with Comparative Examples 5-9 to evaluate the synergistic effect of EVA and LDPE. The notched impact strength of a simply supported beam at -30℃ was 5.6 kJ / m² when no transition coating was applied, EVA was used only, LDPE was used only, reverse sequential coating was applied, and direct blending was performed without pre-coating. 2 6.2kJ / m 2 6.5kJ / m 2 5.9kJ / m 2 and 7.4 kJ / m 2 All were lower than the 8.7 kJ / m³ of Example 1. 2 The vinyl acetate structural units in the inner layer of EVA have a certain degree of polarity, which can improve its wetting of the KH-560 and carboxylated styrene-butadiene latex coating surfaces, and reduce microporosity and interface abrupt changes near the fibers. The outer layer of LDPE contains a large number of ethylene segments, which have good segment affinity with the outer PP, POE and LLDPE phases, and are conducive to the formation of continuous polyolefin transition regions during melt processing. The combination of the two in the order of EVA inside and LDPE outside can gradually transition the polarity and modulus of the fiber surface to the non-polar polyolefin matrix, relieve the local constraint of the high-modulus basalt fiber on the adjacent POE / LLDPE flexible phase, and enable the flexible phase to undergo more complete deformation and energy dissipation during low-temperature impact.
[0078] When EVA is used alone, the wetting of the inner side of the fiber is improved, but the bonding between the outer surface of EVA and the non-polar polyolefin matrix is still insufficient. When LDPE is used alone, the compatibility of the outer polyolefin is good, but its wetting ability on the fiber surface containing silane and carboxyl styrene-butadiene latex is insufficient. Reverse coating places LDPE on the inner side, which requires polar wetting, and EVA on the outer side, which requires non-polar bonding, and the positional functions of the two materials are not fully utilized. Although the formulation composition is the same when directly blended, EVA and LDPE are mainly randomly dispersed in the melt and are difficult to stably accumulate around the fiber.
[0079] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material, characterized in that, Includes the following steps: (1) Ethylene-octene copolymer polyolefin elastomer, linear low-density polyethylene, maleic anhydride, styrene and dicumyl peroxide are reacted and extruded, and then devolatilized and granulated to obtain low-temperature resistant polyolefin modified particles. (2) The unsized basalt short-cut fibers were treated with the hydrolysate of γ-glycidyl oxypropyltrimethoxysilane, and then the basalt short-cut fibers were coated with carboxylated styrene-butadiene latex containing 2-methylimidazole. After dehydration and heat treatment, elastic coated basalt fibers were obtained. (3) The elastic coated basalt fiber is first melt-coated with ethylene-vinyl acetate copolymer, and then melt-coated with low-density polyethylene after cooling to obtain sequentially coated fiber masterbatch; (4) The polypropylene and the low-temperature resistant polyolefin modified particles are melt-mixed, and the sequentially coated fiber masterbatch is added in the later stage of the melt mixing. The mixture is then extruded and granulated to obtain the polypropylene safety helmet shell material.
2. The preparation method according to claim 1, characterized in that, In step (1), based on a total of 100 parts by mass of the ethylene-octene copolymer polyolefin elastomer and linear low-density polyethylene, the ethylene-octene copolymer polyolefin elastomer comprises 75-85 parts by mass, the linear low-density polyethylene comprises 15-25 parts by mass, the maleic anhydride comprises 1.0-1.3 parts by mass, the styrene comprises 1.05-1.40 parts by mass, and the dicumyl peroxide comprises 0.06-0.10 parts by mass as an effective component; the molar ratio of maleic anhydride to styrene is 0.9:1 to 1.1:
1.
3. The preparation method according to claim 2, characterized in that, Step (1) includes: Maleic anhydride is added to styrene and stirred at 55-60°C under nitrogen protection to form a clear solution; the ethylene-octene copolymer polyolefin elastomer and linear low-density polyethylene are added to a twin-screw extruder and, after they melt, the clear solution is injected into the reaction section filled with polymer melt, and dicumyl peroxide is added by an independent feeding device. The melt temperature in the reaction section is 177-183℃, and the residence time of the material in the reaction section is 90-120 seconds. After the reaction is completed, the material is devolatilized under a gauge pressure of -0.08 to -0.06 MPa, and then 0.08-0.12 parts by weight of antioxidant 1010 and antioxidant 168 are added. The mixture is then extruded and granulated.
4. The preparation method according to claim 1, characterized in that, In step (2), the basalt short-cut fiber is 100 parts by weight, the γ-glycidyl etheroxypropyltrimethoxysilane is 0.8 to 1.0 parts by weight, the carboxylated styrene-butadiene latex is 8 parts by weight based on dry rubber, and the 2-methylimidazole is 0.016 to 0.020 parts by weight. The basalt short-cut fibers have a length of 2-4 mm and a single filament diameter of 9-17 μm; the carboxylated styrene-butadiene latex has a dry amino acid value of 20-30 mg KOH / g, a gel content of not less than 80%, and a glass transition temperature of not more than -30℃.
5. The preparation method according to claim 4, characterized in that, Step (2) includes: The γ-glycidyl etheroxypropyltrimethoxysilane was prepared into an ethanol / water solution with a mass concentration of 8% to 12%, wherein the mass ratio of ethanol to water was 95:
5. The pH value was adjusted to 4.5 to 5.0 with acetic acid. After pre-hydrolyzing at 25°C for 20 to 30 minutes, it was sprayed onto the surface of basalt chopped fibers, dried at 80°C for 1 hour, and then treated at 105 to 110°C for 30 minutes. 2-Methylimidazole was dissolved in water and then added to carboxylated styrene-butadiene latex. The resulting carboxylated styrene-butadiene latex was sprayed onto the surface of basalt short-cut fibers treated with the hydrolysate. The fibers were first dehydrated at 60–80°C, then heat-treated at 135–145°C for 45–60 minutes under nitrogen protection, and finally vacuum dried until the moisture content was no higher than 0.2%.
6. The preparation method according to claim 1, characterized in that, In step (3), the polypropylene used in step (4) is 100 parts by mass, the elastic coated basalt fiber is 8 to 12 parts by mass, the ethylene-vinyl acetate copolymer is 1.2 to 2.0 parts by mass, and the low-density polyethylene is 1.6 to 2.8 parts by mass. The ethylene-vinyl acetate copolymer has a vinyl acetate content of 14% to 18% and a melt mass flow rate of 6 to 12 g / 10 min at 190°C and 2.16 kg load. The low-density polyethylene is a long-branched ethylene homopolymer obtained by high-pressure free radical polymerization, with a density of 0.918–0.924 g / cm³. 3 The melt mass flow rate at 190℃ and 2.16kg load is 4~10g / 10min.
7. The preparation method according to claim 6, characterized in that, Step (3) includes: Ethylene-vinyl acetate copolymer with a particle size of no more than 300 μm was added to the elastically coated basalt fiber and mixed at 108–118 °C and 60–100 r / min for 6–8 minutes. After the first melt coating was completed, the mixture was cooled to below 40 °C. Then add low-density polyethylene with a particle size of no more than 300 μm, mix at 125-135℃ and 60-100 r / min for 5-8 minutes, cool after the second melt coating is completed, and obtain the sequentially coated fiber masterbatch.
8. The preparation method according to claim 1, characterized in that, In step (4), polypropylene is 100 parts by weight, and the low-temperature resistant polyolefin modified particles are 12-16 parts by weight; the sequentially coated fiber masterbatch includes 8-12 parts by weight of elastic coated basalt fiber, 1.2-2.0 parts by weight of ethylene-vinyl acetate copolymer and 1.6-2.8 parts by weight of low-density polyethylene; antioxidant 1010 and antioxidant 168 are also added in 0.15-0.20 parts by weight each. The polypropylene, low-temperature resistant polyolefin modified particles, antioxidant 1010 and antioxidant 168 are added from the main feed port of the twin-screw extruder, and the sequentially coated fiber masterbatch is added from the rear side feed port after the vacuum devouring port. The temperatures of each zone of the twin-screw extruder are 150–160℃, 165–175℃, 175–185℃, 185–195℃, 185–195℃, and 180–190℃ respectively, and the melt temperature is not higher than 195℃. The residence time after the sequentially coated fiber masterbatch is added is 30–60 seconds.
9. The preparation method according to claim 8, characterized in that, It also includes drying the polypropylene helmet shell material obtained in step (4) at 75-85°C for 2 hours and then injection molding it to obtain a polypropylene helmet shell; The injection molding machine has a barrel temperature of 175–195℃, a melt temperature not exceeding 195℃, a mold temperature of 35–45℃, an injection pressure of 70–90MPa, a holding time of 8–12 seconds, and a cooling time of 20–35 seconds.
10. A low-temperature resistant, high-impact, high-performance polypropylene safety helmet shell material, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.